Habitat use and reproductive success of ospreys in central interior California - Daniel Airola; James A. Estep, (California Fish and Wildlife Journal, 2022)
The osprey (Pandion halieatus) declined globally in the mid-late 20th century due primarily to pesticide contamination that reduced reproduction. The species has recovered through much of its range, and its range in California has increased. The species has received limited attention in recent decades, despite recommendations that it be monitored as an environmental indicator. In 2021, we located a sample of 39 osprey occupied nests near the Sacramento River and at reservoirs and small ponds in central interior California and determined habitats used and reproductive success. Nearly one-third of nests were located within 100 m of waterbodies and 88% were within 1000 m. The median distance of nests from roads was 51 m. Thirty-four (87%) of occupied nests were on anthropogenic sites, including utility poles, poles erected for ospreys, transmission towers, light poles, and port structures. Only five nests (13%) were in trees and snags. Nearly half (48%) of nests were on platforms constructed on utility poles and on poles erected for ospreys, both placed to protect electrical systems. Water levels in reservoirs, and some small farm ponds, were lower than average in 2021 due to drought, while the Sacramento River and Port were less affected. Twenty-four (71%) of 34 adequately monitored nests were successful in fledging at least one young. Productivity averaged 1.27 young/occupied nest, suggesting a healthy population. Reproductive success differed significantly among nests at different water body types, with river-port, reservoir, and pond sites exhibiting high, moderate, and low productivity, respectively. Our results document a range expansion into central interior California, presumably in response to reduced pesticide levels, reservoir creation, and availability of anthropogenic nest sites. Results also suggest that drought, and thus predicted warming and drier climate, may disproportionately affect populations nesting at non-riverine habitats by reducing the amount foraging area and increasing the distance from nest sites to foraging areas.